The incidence of concussion in professional and collegiate ice hockey: are we making progress? A systematic review of the literature - Ruhe, A.; Gänsslen, A.; Klein, W. (British Journal of Sports Medicine, 2014)
Background: The fast, random nature and characteristics of ice hockey make injury prevention a challenge as high-velocity impacts with players, sticks and boards occur and may result in a variety of injuries, including concussion. Methods: Five online databases (January 1970 and May 2012) were systematically searched followed by a manual search of retrieved papers. Results: Seventeen studies met the inclusion criteria. The heterogeneous diagnostic procedures and criteria for concussion prevented a pooling of data. When comparing the injury data of European and North American or Canadian leagues, the latter show a higher percentage of concussions in relation to the overall number of injuries (2-7% compared with 5.3-18.6%). The incidence ranged from 0.2/1000 to 6.5/1000 game-hours, 0.72/1000 to 1.81/1000 athlete-exposures and was estimated at 0.1/1000 practice-hours. Discussion and conclusions: The included studies indicate a high incidence of concussion in professional and collegiate ice hockey. Despite all efforts there is no conclusive evidence that rule changes or other measures lead to a decrease in the actual incidence of concussions over the last few decades. This review supports the need for standardisation of the diagnostic criteria and reporting protocols for concussion to allow interstudy comparisons in the future.